Shear properties of the strain hardening cementitious composite material - Baghi, Hadi (2016)
Recently, Strain Hardening Cementitious Composite (SHCC) material has been used for the shear strengthening and the structural rehabilitation of reinforced concrete structures. However, the shear behavior of this material has not been yet fully understood due to lack of an appropriate and accurate direct shear test method. This paper aims to investigate the shear properties of the SHCC material. For this purpose, Iosipescu shear test was selected, where loads are applied in antisymmetric four points bending, assuring a pure shear section at the center of the specimen. A special geometry for the specimen was adopted in order to assure a uniform shear stress distribution in the pure shear section. This experimental test can characterize the shear behavior of SHCC material. The experimental test was simulated by the FEM-based computer program, FEMIX. To predict the average shear stress-sliding response, the shear crack softening diagram, available in the multi-directional fixed smeared crack model, was used. After demonstration the good predictive performance of the numerical model, a parametric study was carried out to evaluate the influence of shear retention factor, fracture energy of mode II, and crack shear strength on the average shear stress-sliding response of the SHCC. The advantage of SHCC instead of conventional mortar was also studied.